2022
DOI: 10.1097/ajp.0000000000001028
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a New Sustained-release Pregabalin Formulation Compared With Immediate-release Pregabalin in Patients With Peripheral Neuropathic Pain

Abstract: Objective: This study investigated whether a new sustained-release (SR) pregabalin formulation is noninferior to immediate-release (IR) pregabalin in alleviating peripheral neuropathic pain in Korean patients. Materials and Methods: This was a randomized, double-blind, active-controlled phase 3 study of patients with diabetic peripheral neuropathy or postherpetic neuralgia from 41 sites in South Korea in 2017-2018. Eligible patients were randomized (1:1) to receive once-daily SR pregabalin or twice-daily IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The complete list of included articles with detailed characteristics (pharmacological target, drug, route, dosage, clinical trial code, phase and completion date) is shown in Table 1 . The most repeated main pharmacological target, referring to the one that explains the analgesic effect, was subunit α2δ of voltage-gated calcium channels (VGCCs) [ 13 , 14 , 15 , 16 , 17 , 18 ], which was followed by Voltage-Gated Sodium Channels (VGSCs) in its different subtypes [ 19 , 20 ] and mu opioid receptor [ 21 , 22 , 23 ]. Other mechanisms included were Angiotensin II Type 2 Receptor (AT2R) [ 24 ], Cyclooxygenase-1 (COX-1) [ 25 ], Adaptor-Associated Kinase 1 (AAK1) [ 26 ], Lanthionine Synthetase Component C-like protein (LANCL) [ 27 ], an unknown mechanism [ 28 ], N-Methyl-D-Aspartate Receptor (NMDAR) [ 29 ] and Nerve Growth Factor (NGF) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The complete list of included articles with detailed characteristics (pharmacological target, drug, route, dosage, clinical trial code, phase and completion date) is shown in Table 1 . The most repeated main pharmacological target, referring to the one that explains the analgesic effect, was subunit α2δ of voltage-gated calcium channels (VGCCs) [ 13 , 14 , 15 , 16 , 17 , 18 ], which was followed by Voltage-Gated Sodium Channels (VGSCs) in its different subtypes [ 19 , 20 ] and mu opioid receptor [ 21 , 22 , 23 ]. Other mechanisms included were Angiotensin II Type 2 Receptor (AT2R) [ 24 ], Cyclooxygenase-1 (COX-1) [ 25 ], Adaptor-Associated Kinase 1 (AAK1) [ 26 ], Lanthionine Synthetase Component C-like protein (LANCL) [ 27 ], an unknown mechanism [ 28 ], N-Methyl-D-Aspartate Receptor (NMDAR) [ 29 ] and Nerve Growth Factor (NGF) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…[21] In a previous randomized double-blind study in South Korean patients with DPN and postherpetic neuralgia, the efficacy of the new SR pregabalin (YHD1119), as measured by the mean Daily Pain Rating Scale score, was non-inferior to IR pregabalin. [15] However, there was no assessment of drug compliance when the IR formulation is switched to the SR formulation from twice-daily to once-daily dosing.…”
Section: Discussionmentioning
confidence: 99%
“…was shown to be effective and safe in a randomized, non-inferiority phase 3 study conducted in Korea. [15] However, there is limited real-world data comparing the efficacy, safety, and medication adherence between immediate-release (IR) and SR formulations of pregabalin. Therefore, in this study, we aim to evaluate the efficacy, safety, and medication adherence of pregabalin SR compared with those of pregabalin IR.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many treatment methods for PHN, and the rational selection of drugs is the basis for the treatment of patients with PHN. Compared with other treatment methods such as interventional therapy, drug therapy is relatively simple, safe, and easy to manage, with higher patient compliance, better treatment effects, and is more conducive to the remission of the disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%